The efficacy of bracing painful wrists in gymnasts 8-22 years whilst they are performing gymnastic activities - Trevithick, B. (University of the Sunshine Coast, 2020)
Participation in gymnastics requires gymnasts to weight bear through their upper limb. Combined with training intensity and growth spurts in the skeletally immature cohort, the wrist is subject to repetitive compressive loading which predisposes pain, overuse and injury. Management of gymnast`s wrist pain is both a diagnostic and therapeutic challenge with little known about the efficacy of injury prevention strategies. Having observed the increased evidence of wrist pain and consequent injuries in young gymnasts presenting in my physiotherapy clinic, concerns were raised about whether this increase was a local phenomenon or a general trend across gymnastic clubs. Also, of concern was the apparent lack of reporting of wrist pain till an injury occurred, the self-management and the indiscriminate use of wrist braces with little or no monitoring of their efficacy in decreasing wrist pain or as an injury prevention device. To address these concerns, three clinical studies and a case study were conducted. Approval for all studies was granted by the Human Research Ethics Committee of the University of the Sunshine Coast S/12/446. The initial study collated 237 survey responses from Australian artistic gymnasts 10-18 years to determine the prevalence of wrist pain experienced by Australian gymnasts. Results show that prevalence of wrist pain was high across all levels of gymnastics with a lifetime prevalence of 92.6% and point prevalence of 70.6% recorded. The apparatus most reported as contributing to wrist pain in males was the pommel (75%) and the floor in females (63%). Wrist braces was shown to be the treatment choice for wrist pain; however, further evidence is needed, prompting the research into the efficacy of wrist braces to decrease the experience of wrist pain whilst performing gymnastics (Study 4). As wrist loading is acknowledged as a predisposing factor in the development of gymnasts wrist pain, the second study determined normative ground reaction force (GRF), centre of pressure (COP), and wrist kinematic and kinetic data occurring at the wrist while fifteen gymnasts (10-17 years) performed a static handstand over 8s. To investigate changes in some key biomechanics data with increased skills, further data was collected while gymnasts performed handwalking and front and back handsprings. These data were compared to gymnast with wrist pain who demonstrated sway outside the normative data, poor balance and technique. The increase in ground reaction forces for handwalking, front handspring and back handsprings was recorded. How chronic wrist pain may affect basic skill technique and alter normal movement patterns led to the third study (Case study). This study discusses the management of a national gymnast who trained with wrist pain and subsequently sustained an injury. An outcome of this study has been the design of an Injury Report form to include documentation and monitoring of wrist pain before time loss is required or an injury occurs. Included in the gymnast`s rehabilitation was the short use of a wrist brace. To assess any brace influence on wrist pain, the ground reaction forces were recorded while the gymnasts performed a handstand, initially without the braces then wearing the braces. Although there were no significant differences in the handstand GRF data recorded for this gymnast and the normative handstand data established in Study 2, the gymnast`s wrist pain was decreased, and technique improved. To further test the efficacy of this design of wrist brace in decreasing wrist pain in a gymnastic setting, the fourth study was completed. The wrist wrap brace with a 4.8mm volar gel pad was trialled over three weeks by 48 male gymnasts (10-22 years) who experienced wrist pain when performing gymnastics. Overall wrist pain (visual analogue scale VAS) was recorded pre and post-trial then analysed to quantify the relative magnitude of differences. Gymnasts reported significantly reduced experience of wrist pain (p = 0.002, 53.5%) when performing on the pommel, floor and parallel bars. The overall effect size was practically significant (d = 0.902). Therefore, the wrist brace design was found to be effective in reducing painful wrists in 53% of the male gymnasts whilst performing gymnastic activities.